Challenges in Detecting Ecological Interactions Using Sedimentary Ancient DNA Data - Fiona Margaret Callahan; Jacky Kaiyuan Li; Rasmus Nielsen (Environmental DNA)
ABSTRACT With increasing availability of ancient and modern environmental DNA technology, whole‐community species occurrence and abundance data over time and space is becoming more available. Sedimentary ancient DNA data can be used to infer associations between species, which can generate hypotheses about biotic interactions, a key part of ecosystem function and biodiversity science. Here, we have developed a realistic simulation to evaluate five common methods from different fields for this type of inference. We find that across all methods tested, false discovery rates of interspecies associations are high under simulation conditions where the assumptions of the methods are violated in a variety of ecologically realistic ways. Additionally, we find that for more realistic simulation scenarios, with sample sizes that are currently realistic for this type of data, models are typically unable to detect interactions better than random assignment of associations. Different methods perform differentially well depending on the number of taxa in the dataset. Some methods (SPIEC‐EASI, SparCC) assume that there are large numbers of taxa in the dataset, and we find that SPIEC‐EASI is highly sensitive to this assumption while SparCC is not. Additionally, we find that for many methods, default calibration can result in high false discovery rates. We find that for small numbers of species, no method consistently outperforms logistic and linear regression, indicating a need for further testing and methods development.